Teachers' Perspectives on Using STEM in English Language Teaching in Elementary School - Budiarto, Teguh; Usadiati, Wahyuningsih; Sholeh, Agus (Language Circle: Journal of Language and Literature, 2025)
STEM education incorporates Science, Technology, Engineering, and Mathematics into a single learning paradigm. Through investigation, experimentation, and design-based problem solving, this method helps students develop critical, creative, and collaborative thinking. STEM principles can be used in English Language Teaching as well as other fields. STEM can make language learning more relevant and practical while developing 21st-century abilities. This study examines the perspectives of teachers in public primary school of Dadapan, Malang, Indonesia  on integrating STEM into their English language teaching. It also analyzed their readiness to implement this approach. This study used qualitative descriptive design, where the researcher used a questionnaire, interview, and observation as the instruments to collect the data, and employed thematic analysis and triangulation for analysing the data. This study reveals that (1). The teachers have a strong understanding of the concept of STEM and believe that it is a valuable and effective method for teaching English. Moreover, it has a favorable impact on students' ground, engagement, and overall academic performance. (2). The majority of teachers demonstrate preparedness for this integration. However, they clearly indicated a significant need for increased cooperation among colleagues, more accessible resources and instructional materials, and continuous professional training. The findings of this study provide practical guidance for curriculum developers and teachers on how to effectively integrate STEM into English language lessons, especially in the elementary education level.